2020
DOI: 10.2478/rjim-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Role of urinary podocalyxin in early diagnosis of diabetic nephropathy

Abstract: Introduction: Podocyte injury has been reported as an early feature of DN therefore, the assessment of podocyte injury can be accomplished by estimation of podocalyxin in urine. This study aimed to estimate the urinary podocalyxin levels and to determine the sensitivity and specificity of this biomarker for early detection of DN.Materials and methods: A total of 90 patients with type 2 diabetes mellitus (T2DM) were included in this cross-sectional study. Sixty of them were without diagnosed DN, and 30 with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
4
14
1
1
Order By: Relevance
“…7 Presence of podocyturia has also been reported previously in patients with DKD. 7,[44][45][46] Furthermore, our previous study (submitted paper under review) confirms the main findings consistent with the literature in a larger diabetic patient group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…7 Presence of podocyturia has also been reported previously in patients with DKD. 7,[44][45][46] Furthermore, our previous study (submitted paper under review) confirms the main findings consistent with the literature in a larger diabetic patient group.…”
Section: Discussionsupporting
confidence: 90%
“…Nakamura et al identified podocytes in the urine of patients with micro‐ and macroalbuminuria, and it was also thought that depending on the severity of glomerular damage, the level of podocyturia can change 7 . Presence of podocyturia has also been reported previously in patients with DKD 7,44‐46 . Furthermore, our previous study (submitted paper under review) confirms the main findings consistent with the literature in a larger diabetic patient group.…”
Section: Discussionsupporting
confidence: 89%
“…An important finding of the present study was that the case group had higher S.PCX levels than the control group. Similar results were found by (Kostovska et al, 2020;Shelbaya et al, 2020), who reported that urinary podocalyxin (U.PCX) levels were higher in diabetic patients. In addition, higher S.PCX levels were found in patients with macroalbuminuria than in those with normoalbuminuria and microalbuminuria but statistically not significant.…”
Section: Discussionsupporting
confidence: 87%
“…DN is a leading cause of the end-stage renal disease (ESRD) and is defined clinically by elevated urinary albumin excretion or/and the presence of impaired renal function (Barutta et al, 2021). Besides increased albuminuria and a decreased estimated glomerular filtration rate (eGFR), the two common indicators of DN (Cole and Florez, 2020), some studies have confirmed the existence of a new biomarker called podocalyxin (Shoji et al, 2016;Kostovska et al, 2020;Shelbaya et al, 2020;Ghorab et al, 2020;Xie et al, 2021). They measured podocalyxin levels in the urine and confirmed its positive correlation with UACR.…”
Section: Introductionmentioning
confidence: 96%
“…(7) [8] [9] [10][11] [12] [13][14].The molecular weight of the peptide bone of podocalyxin is 55 kDa which is 200 kDa with heavy glycosylation. Serum podocalyxin (likely derived from maternal endothelial cells) levels increase throughout pregnancy, and it is possible that the non-glycosylated form can be filtered through the glomerular filtration barrier when higher serum levels are present, resulting in increased urinary excretion [15].…”
mentioning
confidence: 99%